2014
DOI: 10.3382/ps.2014-03961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the composition of the basal diet on the evaluation of mineral phosphorus sources and interactions with phytate hydrolysis in broilers

Abstract: The objectives of this study were to determine the availability of P from mineral phosphate sources by using different basal diets and measurement of P retention and prececal (pc) P digestibility as well as pc myo-inositol phosphate (InsP) degradation in broilers. Semi-synthetic and corn-soybean meal-based basal diets were used in experiment 1, and corn-based and wheat-based basal diets were used in experiment 2. Anhydrous monosodium phosphate (MSPa) or monocalcium phosphate monohydrate (MCPh) was supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 33 publications
6
45
0
Order By: Relevance
“…In contrast, crop InsP 6 hydrolysis in the present study was high (59%) when a wheat-based diet with intrinsic phytase activity (623 U/kg) was fed to birds in Experiment 1. Several recent studies found no relation between dietary intrinsic phytase activity and InsP 6 hydrolysis in the ileum of broilers (Leytem et al 2008;Shastak et al 2014). This pH is likely to support the activity of wheat phytases, which under in vitro conditions were shown to exhibit maximal activity at pH 6.0 (phytase 1) and pH 5.5 (phytase 2) in a study by Nakano et al (1999).…”
Section: Variability Of Insp 6 Hydrolysis In the Cropmentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast, crop InsP 6 hydrolysis in the present study was high (59%) when a wheat-based diet with intrinsic phytase activity (623 U/kg) was fed to birds in Experiment 1. Several recent studies found no relation between dietary intrinsic phytase activity and InsP 6 hydrolysis in the ileum of broilers (Leytem et al 2008;Shastak et al 2014). This pH is likely to support the activity of wheat phytases, which under in vitro conditions were shown to exhibit maximal activity at pH 6.0 (phytase 1) and pH 5.5 (phytase 2) in a study by Nakano et al (1999).…”
Section: Variability Of Insp 6 Hydrolysis In the Cropmentioning
confidence: 82%
“…The pH measured in the digesta from the crop in Experiment 1 averaged 5.3 (SD 0.42) (treatment means did not differ significantly (data not shown)). However, InsP 6 hydrolysis by microbiota-and mucosa- associated phytases in the small intestine might compensate for the lack of crop hydrolysis in the absence of intrinsic plant phytase and likely explains why the degree of InsP 6 hydrolysis measured in the terminal ileum of broilers was not lower when a wheat-based diet was fed compared to a maize-based diet (Shastak et al 2014). Comparatively, the far lower InsP 6 hydrolysis in birds fed BD TW (26%) compared to birds fed BD UTW was most likely the consequence of the lower activities of intrinsic wheat phytase and other enzymes following microwave treatment.…”
Section: Variability Of Insp 6 Hydrolysis In the Cropmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, an understanding of the inhibitory effects of several factors on InsP 6 disappearance in the digestive tract is important. Previous studies have found negative effects of P and calcium (Ca) additions to poultry diets on InsP 6 disappearance in the gastrointestinal tract (GIT) . In contrast, the addition of microbial phytases ( myo ‐inositol hexaphosphate phosphohydrolases) to feed results in increased availability of P from plant ingredients, and complexes between phytate and other minerals might be diminished .…”
Section: Introductionmentioning
confidence: 99%
“…Gao et al (2013) used an even lower NPP level (1.0 g/kg, total phosphorus 3.4 g/kg) than in this study, and they also reported a higher coefficient of apparent ileal digestibility of phosphorus from this diet (0.506) compared with phosphorus digestibility from diet with total phosphorus 5.7 g/kg and 3.2 NPP g/kg (0.474). Thus, it can be inferred that the digestibility of phytate phosphorus in Zeller et al (2015) and Shastak et al (2014) who published that mineral phosphorus supplementation reduces the degradation of myoinositol phosphates. On the other hand, Hafeez et al (2016) also published very similar coefficients of apparent ileal phosphorus digestibility in layer diets (from 0.311 to 0.409).…”
Section: Discussionmentioning
confidence: 99%